Alzheimer's disease associated AKAP9 I2558M mutation alters posttranslational modification and interactome of tau and cellular functions in CRISPR‐edited human neuronal cells. Issue 6 (14th May 2022) - You, Yang; Hersh, Samuel W.; Aslebagh, Roshanak; Shaffer, Scott A.; Ikezu, Seiko; Mez, Jesse; Lunetta, Kathryn L.; Logue, Mark W.; Farrer, Lindsay A.; Ikezu, Tsuneya
Abstract: Alzheimer's disease (AD) is a pervasive neurodegeneration disease with high heritability. In this study, we employed CRISPR‐Cas9‐engineered technology to investigate the effects of a rare mutation (rs144662445) in the A kinase anchoring protein 9 ( AKAP9 ) gene, which is associated with AD in African Americans (AA), on tau pathology and the tau interactome in SH‐SY5Y P301L neuron‐like cells. The mutation significantly increased the level of phosphorylated tau, specifically at the site Ser396/Ser404. Moreover, analyses of the tau interactome measured by affinity purification‐mass spectrometry revealed that differentially expressed tau‐interacting proteins in AKAP9 mutant cells were associated with RNA translation, RNA localization and oxidative activity, recapitulating the tau interactome signature previously reported with human AD brain samples. Importantly, these results were further validated by functional studies showing a significant reduction in protein synthesis activity and excessive oxidative stress in AKAP9 mutant compared with wild type cells in a tau‐dependent manner, which are mirrored with pathological phenotype frequently seen in AD. Our results demonstrated specific effects of rs14462445 on mis‐processing of tau and suggest a potential role of AKAP9 in AD pathogenesis. Abstract : Alzheimer's disease (AD) is the most common form of dementia with a high genetic influence. A previous study identified a rare variant (rs144662445) in AKAP9 (a kinase anchor protein 9) conferred a high risk for AD in African American population, suggesting a pathogenic role of AKAP9  mutation. By using CRISPR‐edited human neuronal cells, this study revealed specific effects of rs14462445 on mis‐processing of tau and recapitulation of phenotypes observed in AD, including dysregulation of protein synthesis and excessive oxidative stress.